Randomized Clinical Trials in Stem Cell Therapy for the Heart - Old and New Types of Cells for Cardiovascular Repair - Sanz-Ruiz, Ricardo; Arranz, Adolfo Villa; Ibañes, Enrique Gutiérrez; Santos, María Eugenia Fernández; Fernández, Pedro Luis Sánchez; Fernández-Avilés, Francisco (IntechOpen, 2011)
None